CORTICOSTEROID THERAPY ASSOCIATED WITH COVID-19: AN ALLY OR A RISK FACTOR FOR THE ESTABLISHMENT OF SECONDARY FUNGAL CO-INFECTIONS? An allied or a risk factor for the secundary fungal co-infections establishment? - Ferreira do Amaral, Thaís; Monteiro da Silva Rodrigues Coutinho, Natália; do Nascimento Fuentefria, Rubia; Meneghello Fuentefria, Alexandre; Machado, Gabriella da Rosa Monte Machado (Clinical and Biomedical Research, 2023)
Introduction: the corticosteroids therapy to combat inflammation caused by SARS-CoV-2 appears to be a risk factor for the secondary fungal co-infections development. Methods: pubmed and science direct databases, using the following words group: [(aspergillosis OR mucormycosis OR candidiasis) AND (coronavirus disease) AND (corticoids) were used for this review. The selected articles present the main risk factors related to the secondary fungal co-infections establishment in COVID-19 patients. Results: the corticosteroid therapy use to combat inflammation caused by SARS-CoV-2 has been shown to be strongly associated with mucormycosis and aspergillosis establishment. Mucormycosis has been the main fungal co-infection related to corticosteroid therapy, causing a greater number of deaths in COVID-19 patients. Diabetes mellitus was the most prevalent comorbidity, mainly for the mucormycosis establishment. The dexamethasone use seems to be associated with the mucormycosis emergence and to death. However, aspergillosis showed a greater relationship with patient recovery. Thus, risk factors such as diabetes mellitus, combined with corticosteroids use, have shown a relationship to the mucormycosis establishment. Conclusion: the corticosteroids use in COVID-19 patients should be individually analyzed, taking into account mainly the patient’s medical history and the risk/benefit ratio of the use of these drugs.